Konsep Fisika dalam Produksi Bakpia Tradisional: Eksplorasi Proses Kuliner Lokal sebagai Sumber Pembelajaran Kontekstual - Lintang Auliya Kurdiati (PendIPA Journal of Science Education, 2026)
Traditional culinary practices often involve physics processes that can be interpreted through scientific principles, yet these phenomena are rarely explored as contextual learning resources in physics education. This study aims to identify and analyze physics concepts embedded in the traditional production of bakpia, a well-known local pastry from Yogyakarta, Indonesia. The research employed a qualitative descriptive approach through direct observation and documentation of the dough mixing and roasting stages in a local bakpia production setting. The observed processes were then analyzed using fundamental physics concepts, particularly in the domains of mechanics and heat transfer. The results indicate that the dough mixing stage reflects principles of rotational motion, pulley transmission, angular velocity, frictional interaction, and mechanical power, while the roasting stage demonstrates multiple heat transfer mechanisms, including conduction, convection, and radiation. These findings reveal that traditional bakpia production inherently embodies scientific principles that can be explained through physics concepts. The study highlights the potential of local culinary practices as meaningful contextual resources for physics learning, contributing to the development of culturally relevant and context-based science education.